INDIVIDUALIZATION OF PROFESSIONAL EDUCATION PROCESS ON THE BASIS OF DIGITAL TECHNOLOGIES - Shaxnoza Abduhakimovna Abduraxmanova (Scholar Express Journal, 2022)
In the digital economy, the development of skills in the use of digital technologies should be carried out mainly in the education system, especially in the vocational education system, by combining these skills with practice.
Keywords: Digital Economy; Education system; skills; education